High voltage measurement, testing and design - Gallagher, T. J.; Pearmain, A. J. ([S.l.] : Wiley, 1984)
Provides a brief, historical account of the development of high-voltage technology and a perspective of equipment used. Surveys the mechanisms of breakdown under high electric stresses and describes experimental and theoretical techniques which permit these stresses to be estimated. Discusses methods for generating and measuring high voltages, and high potential testing of equipment. Includes problems at the end of the text.